Sobrevivencia y crecimiento inicial en diámetro – altura para Cedrelinga cateniformis ducke en diferentes proporciones de “gallinaza” en vivero. Puerto Almendra, Loreto, Perú – 2023 - Orbe Vargas, Marlon Anthony (2025)
The objective of this study was to evaluate the survival rate and the initial growth in height and diameter of Cedrelinga cateniformis Ducke “tornillo” seedlings under different proportions of poultry manure in a nursery, conducted in Puerto Almendras, Loreto, Peru – 2023. Four treatments were designed using mixtures of natural soil, white sand, and poultry manure in varying proportions (80%, 60%, 40%, and 20% poultry manure), along with a control consisting exclusively of natural soil. Throughout the trial, periodic measurements of seedling height, diameter, and survival were recorded. The results showed that the greatest increase in height was obtained in the control group, with an average of 13.6 cm, whereas the largest diameters were observed in the treatments with 60% and 40% poultry manure, both averaging 1.2 mm. Regarding survival, the highest value was also recorded in the control with 86.7% of seedlings alive. However, statistical analysis revealed no significant differences among treatments for any of the evaluated variables (p<0.05). These findings indicate that Cedrelinga cateniformis has a high adaptability in nursery conditions and that the use of poultry manure does not provide significant advantages over natural soil. Consequently, it is concluded that natural soil alone is sufficient to ensure adequate early growth and high survival, representing a practical and cost-effective alternative for the production of seedlings intended for reforestation programs in the Amazon region.